2022
DOI: 10.1093/ecco-jcc/jjac033
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Circulating Transcriptomic Landscape in Inflammatory Bowel Disease Provides Evidence for Dysregulation of Multiple Transcription Factors Including NFE2, SPI1, CEBPB, and IRF2

Abstract: Aim To assess the pathobiological and translational importance of whole blood transcriptomic analysis in inflammatory bowel disease (IBD). Methods We analyzed whole blood expression profiles from paired-end sequencing in a discovery cohort of 590 Europeans recruited across six countries in the IBD Character initiative (newly diagnosed patients with Crohn’s disease [CD, n = 156], ulcerative colitis [UC, n = 167], and controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Since GPR15 is a homing receptor for lymphocytes into the colon, it is of special importance in the context of the protective influence of smoking against ulcerative colitis. We showed that GPr15 expression in whole blood is associated with smoking in a cohort of patients with IBD (IBD-Character) [13]. A context for the interpretation of this finding was provided by Xiong et al In their experiments AHR activation could increase GPr15 expression in regulatory T lymphocytes, in cooperation with FOXP3, leading to inflow of immunosuppressive GPR15 + T reg cells into the colon [14].…”
Section: Introductionmentioning
confidence: 58%
“…Since GPR15 is a homing receptor for lymphocytes into the colon, it is of special importance in the context of the protective influence of smoking against ulcerative colitis. We showed that GPr15 expression in whole blood is associated with smoking in a cohort of patients with IBD (IBD-Character) [13]. A context for the interpretation of this finding was provided by Xiong et al In their experiments AHR activation could increase GPr15 expression in regulatory T lymphocytes, in cooperation with FOXP3, leading to inflow of immunosuppressive GPR15 + T reg cells into the colon [14].…”
Section: Introductionmentioning
confidence: 58%
“…Studies have shown that IL-4 in UC could induce monocytes and eosinophils to participate in inflammatory response and stimulate mast cell proliferation, thus promoting inflammatory response and aggravating the degree of UC. 78 , 79 The level of peripheral 5-HT, a pro-inflammatory factor, which could regulate cellular immune function, promote emission of IFN-γ and other inflammatory factors, 80 and also aggravate inflammatory response of UC, was positively correlated with the severity of UC, 80 , 81 Taken together, DSS could increase the abundance of Clostridium_sensu_stricto_1 relative pro-inflammatory factors, promotes the release of IL-4, 5-HT, TNF-α and IFN-γ, which could promote intestinal inflammation, leading to ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…SNP-dependent putative transcription factor binding sites were identified by motif analysis. Thirty one TF factors were identified ( Supplemental Table 1 ) of which 50% have been associated with differential gene expression in whole blood from CD compared to non-IBD subjects ( 37 ). All TFs were analyzed for trans eQTL association of expression with RNASET2 disease risk genetic variation carriage.…”
Section: Resultsmentioning
confidence: 99%